Maneckji Limji Hataria and His Iranism Interactions with Elites of the Naaser-al-ddinshah Era (1847-1895) - Hajianpour, Hamid; Aidi, Abdalmajid (Journal of History Culture and Art Research, 2017)
Iranism and its genesis in the history of Iran is one of the issues that has still remained in the dispute. One of the reasons contributing to occur is that there are some ambiguities in the history. Meanwhile, the role of Maneckji Limji Hataria is among the factors that are worthy of further reflection. In 1854 (1270 AH) Maneckji Limji Hataria entered as the first envoy, Parsis of India to Iran. He interacted with the intelligent and writers of Iran society, Naaseri era during his long-term inhabitance there. The present study seeks to answer the question that “what is the position of Iranism and Iranian attitude in his interactions with the intelligent Naaseri era?” For this purpose, referring to historical sources, documents, correspondence and providing evidences, the authors show that Iranism is the basic and fundamental issue in Maneckji Limji Hataria interactions to intellectuals of the Naaseri era and these interactions tend to be considered as a secondary factor affecting the Iranism attitudes of the Naaseri era.